Generational Analysis of Generations of M2 and M3 of Green Beans crop (Vigna radiata L.) Gamma-ray Radiation Results: Analisis Keragaman Fenotipe Generasi M2 Dan M3 Tanaman Kacang Hijau (Vigna radiata L.) Hasil Radiasi Sinar Gamma - Fitri Yanti; Aslim Rasyad; Herman Herman (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2020)
The objective of this research was to determine phenotypic variability of mung bean M2 and M3 Mutant populations resulted from gamma ray irradiation. The Field experiment was conducted by using a completely randomized design in which three populations including M2, M3 and the parent (M0) were planted in 2017. Each population was planted in a plot of 3 m x 2 m with planting space of 30 cm x 20 cm to obtain 100 individual plant per plot. Every population was repeated 5 times so to get 500 plants per population. Observations were collected on all individuals in the population including plant height, number of stem internodes, length of internode, number of primary branches, age of flowering plants, date of harvest, length of pods, number of filled pods, number of seeds per pod, number of seeds per plant, weight of seeds per plants, and weights of 100 seeds. The results showed that gamma ray irradiation produced mung bean plants with a similar date of harvest. It could be seen from mean values ​​which were not significantly different, the values ​​of diversity, and range were almost equal which indicates the diversity of M2, M3 and M0 populations was relatively similar to the control. M2 and M3 generation of mung bean have large and high quality seeds weighing more than 6.5 g/100 seeds. The homogeneity of variance (HOV) analysis showed that variance of all population of all parameters observed were not homogeny except for plant height, number of stem internode and weight of 100 seeds.